2012
DOI: 10.4167/jbv.2012.42.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Community Contaminating Floor of A Hot and Dry Sauna

Abstract: The purpose of this study was to examine profile of bacteria contaminated in a dry sauna. Bacteria sampled from the floor of the dry sauna (75~80℃) were separated and identified by using a thermal gradient gel electrophoresis (TGGE) technique, and were cultivated using a defined medium at 50℃. Bacteria grown in the defined medium were identified based on 16S-rDNA sequence homology. The band number of DNA separated by TGGE was 15, indicating the species diversity of bacteria contaminating the dry sauna. Seven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Another report by Kim et al [26] of a 64ºC dry sauna revealed a population with Firmicutes, Gamma-proteobacteria, Beta-proteobacteria and Deinococci as the most frequent taxa. As mentioned above, our samples were rich Beta-and Gammaproteobacteria, although we also detected Alpha-proteobacteria, which was absent in the works by Kim et al [25] and Lee et al [26]. Reciprocally, we did not detect Firmicutes or Deinococci with our 16S rRNA analysis, while both taxa were found by those two previous reports.…”
Section: S-rdna Analyses With Ion Torrentsupporting
confidence: 66%
See 1 more Smart Citation
“…Another report by Kim et al [26] of a 64ºC dry sauna revealed a population with Firmicutes, Gamma-proteobacteria, Beta-proteobacteria and Deinococci as the most frequent taxa. As mentioned above, our samples were rich Beta-and Gammaproteobacteria, although we also detected Alpha-proteobacteria, which was absent in the works by Kim et al [25] and Lee et al [26]. Reciprocally, we did not detect Firmicutes or Deinococci with our 16S rRNA analysis, while both taxa were found by those two previous reports.…”
Section: S-rdna Analyses With Ion Torrentsupporting
confidence: 66%
“…These results are consistent with previous reports on these two extreme environments. Lee et al [25] characterized the bacterial community contaminating the floor of a hot and dry sauna, which proved rich in Firmicutes, Gamma-proteobacteria and Beta-proteobacteria. Another report by Kim et al [26] of a 64ºC dry sauna revealed a population with Firmicutes, Gamma-proteobacteria, Beta-proteobacteria and Deinococci as the most frequent taxa.…”
Section: S-rdna Analyses With Ion Torrentmentioning
confidence: 99%
“…and Janthinobacterium sp. (Lee and Park 2012 ). Similar trends can be observed for fungi, where more resilient thermotolerant and melanised species, such as Exophiala dermatitidis , Phialophora and Rhinocladiella , often dominate over other yeasts, such as Candida and dermatophytes (Table 1 ) (Novak Babič et al 2017b ).…”
Section: Indoor Environments Dominated By Water-borne Microorganismsmentioning
confidence: 98%
“…Other bacteria were identified as Virgibacillus sp., Tepidomonas sp., Pseudoxanthomonas taiwanensis, Stenotrophomonas sp. and Janthinobacterium sp (Lee and Park 2012)…”
mentioning
confidence: 99%
“…Hot springs and saunas are common thermal environments for normal growth of thermophilic bacteria (Ward et al 1998;Hugenholtz et al 1998). Some thermophilic bacteria have been isolated from a sauna and grew at 60°C (Kim et al 2013a, b;Lee and Park 2012). In this study, we evaluated the possibility of directly preparing soy sauce by submerged fermentation of a defatted soybean meal (DFSM) slurry using thermophilic bacteria but without a process to prepare the meju.…”
Section: Introductionmentioning
confidence: 99%